Trade and development expectations of LDCs - Ahmad Naini (Intereconomics, 1972)
The developing countries are likely to use UNCTAD III to vent their disappointment at this institution's failure in the past to find a satisfactory solution for the questions of trade and development policy which are of interest to them. The great expectations of the developing countries have in fact been left essentially unfulfilled in regard to development aid, lower trade barriers and grant of preferential tariffs for manufactured and semi-manufactured products as well as in the difficult area of raw material policy.
Keywords: 330; Development Policy